Female acts in Greek tragedy - Foley, Helene P., 1942- (Martin classical lectures (Unnumbered)., 2001)
Although Classical Athenian ideology did not permit women to exercise legal, economic, and social autonomy, the tragedies of Aeschylus, Sophocles, and Euripides often represent them as influential social and moral forces in their own right. Scholars have struggled to explain this seeming contradiction. Helene Foley shows how Greek tragedy uses gender relations to explore specific issues in the development of the social, political, and intellectual life in the polis. She investigates three central and problematic areas in which tragic heroines act independently of men: death ritual and lamentat.